Self-control training for school age children in internet addiction prevention effort - Tesha Hestyana Sari; Sri Wahyuni; Fathra Annis Nauli; Jumaini Jumaini; Veny Elita (Community Empowerment, 2022)
Internet addiction can occur in school-age children which has an impact on the inability of children to control themselves from using the internet, causing brain or mental functional problems in everyday life. Community service program is carried out according to the problem, namely educational activities and self-control training for students as an effort to prevent internet addiction. This self-control training was attended by 20 students of SDN 130 Pekanbaru. This program was preceded by health education about internet addiction, then trained students to exercise self-control in using gadgets and the internet and were evaluated after six days of self-control exercises. Programs were measured using a knowledge questionnaire and KDAI internet addiction diagnostic questionnaire as well as the results of a reminder card. The results of the pre-test showed that the average knowledge of the participants was 85.11 and the post-test was 90.82. This program proved to be successful where objectively there was an increase in participants' knowledge about Covid-19 and the use of gadgets.